Chronic, Nonspecific, Postinfectious, Retroperitoneal Fibrosis and Ureteral Obstruction. Issue 2 (April 2016) - Territo, Angelo; Micali, Salvatore; Manenti, Antonio; Martorana, Eugenio; Pirola, Giacomo Maria; Bianchi, Giampaolo
Introduction: Two cases of severe ureteral obstruction following nonspecific, postinfectious, chronic retroperitoneal fibrosis are described, which both originated by a primitive intestinal pathology. Patients: This complication was observed in two women: first, 65 years old, submitted for ulcerative colitis to a total proctocolectomy, with ileo-pouch-anal anastomosis, complicated by an anastomotic fistula; and second, 66 years old, operated with an extended left hemicolectomy, for an adenocarcinoma of the recto-sigmoid colon complicated with a vaginal fistula. In these cases, computerized tomography demonstrated a unilateral hydronephrosis, secondary to a complete obstruction of the ureter; a subsequent nephro-ureterectomy became necessary. Histology demonstrated nonspecific inflammatory lesions. Discussions: Postinfectious, chronic inflammation of the retroperitoneum acts on the ureteral and peri-ureteral tissues, inducing an inflammatory and then a fibrotic process. Conclusions: We underline the opportunity of a precocious and radical treatment of every retroperitoneal infection.